Examination of the Relationship between Anthropometric Characteristics of Elite Wresters and Their Strength and Vertical Jump Performance - Erdal Zorba; Musa Şahin; İsa Doğan; Kürşat Acar (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2021)
The aim of this study was to examine the relation between certain anthropometric characteristics and strength and vertical jump performance of elite wrestlers. 16 athletes wrestling in different clubs participated in our research. Average age of the wrestlers was 23,62 ± 244, while their average height was 177,31 ± 5,18 and their average weight is 86,45 ± 14,91. In determining the anthropometric measurements of the subjects, height, body weight, skin fold thickness, circumference and diameter measurements were made. For measurement of strength parameters, claw strength was measured with a Takkei brand hand dynamometer, while back and leg strength was measured with a back and leg dynamometer. An electronic smart speed lite system was used to measure the vertical jump performance of the athletes. Pearson Correlation Analysis was used to determine the relationship between anthropometric measurements and strength parameters and vertical jump ratios, and values with p <0,05 were considered significant. As a result, the relationship between anthropometric characteristics and physical performance of elite wrestlers was examined, and a high correlation was found between anthropometric measurements and strength parameters. There was no relationship between vertical jump and anthropometric measurements and strength parameters. In addition, it is a remarkable detail that no significant difference could be detected between the leg, back, right and left claw strengths of wrestlers and their anthropometric characteristics.